Health behaviour of Young Adults in a Globalizing World - Urszula Dębska; Halina Guła-Kubiszewska; Wojciech Starościak; Małgorzata Kałwa (Kazimierz Wielki University, 2016)
Purpose: The aim was to diagnose health behaviours in order to predict and plan possible interventions. Methods: Survey, IZZ questionnaire. Material: 1154 students of the University of Physical Education,WrocławUniversity in the years 2015-2016. Results: Gender differences: young men significantly more often declared using non-conventional medicine (the Mann-Whitney U test 3.00; p=.002), but they used stimulants less often than young women (the Mann-Whitney U test 2.51; p=.01). Regular University students - men significantly more often declared care for their mental health (4.196; p=.000), eating habits (3.03; p=.002) then women. Students of the University of Physical Education declared undertaking significantly more activities promoting health with regard to diet (3.94; p=.000), medical behaviour (3.46; p=.000); mental health (3.26; p=.001), non-conventional medicine (2.54; p=.01); stimulants (2.31; p=.02). Among the respondents who did regular exercise, the students of the University significantly more often declared using proper diet (3.46; p=.000), care for their mental health (4.42; p=.000); whereas the students of the University of Physical Education declared taking up active leisure (4.20; p=.000) and eating proper diet (2.46; p=.01).